2017
DOI: 10.1080/10408398.2017.1331200
|View full text |Cite
|
Sign up to set email alerts
|

Food processing strategies to enhance phenolic compounds bioaccessibility and bioavailability in plant-based foods

Abstract: Phenolic compounds are important constituents of plant-based foods, as their presence is related to protective effects on health. To exert their biological activity, phenolic compounds must be released from the matrix during digestion in an absorbable form (bioaccessible) and finally absorbed and transferred to the bloodstream (bioavailable). Chemical structure and matrix interactions are some food-related factors that hamper phenolic compounds bioaccessibility and bioavailability, and that can be counteracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
196
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(203 citation statements)
references
References 129 publications
(144 reference statements)
4
196
0
3
Order By: Relevance
“…These matrix changes probably cause cell wall maceration and increase the extractability of bioactive compounds during digestion, but also higher susceptibility to oxidation and degradation (Oliveira et al ., ). Based on these considerations, significant effects of freezing on polyphenol bioaccessibility could be expected (Ribas‐Agustí et al ., ). Nevertheless, as far as it is known, this is the first study that investigated the effect of different freezing methods on the bioaccessibility of strawberry polyphenols and further studies should be performed to support the findings of this study.…”
Section: Resultsmentioning
confidence: 97%
“…These matrix changes probably cause cell wall maceration and increase the extractability of bioactive compounds during digestion, but also higher susceptibility to oxidation and degradation (Oliveira et al ., ). Based on these considerations, significant effects of freezing on polyphenol bioaccessibility could be expected (Ribas‐Agustí et al ., ). Nevertheless, as far as it is known, this is the first study that investigated the effect of different freezing methods on the bioaccessibility of strawberry polyphenols and further studies should be performed to support the findings of this study.…”
Section: Resultsmentioning
confidence: 97%
“…The impact of processing on the bioaccessibility and bioavailability of phenolic compounds has also been studied by many researchers (Pressman, Clemens, & Hayes, 2017; Ribas‐Agustí, Martín‐Belloso, Soliva‐Fortuny, & Elez‐Martínez, 2017). The reported results have shown that processing of the plant‐based foods can induce some changes in the food matrix, which improve bioaccessibility and bioavailability of polyphenols, such as the chemical transformation into the more bioaccessible and bioavailable forms, weakening of polyphenol interactions with other matrix components, decreasing phytates content by thermal degradation or fermentation, and break of the plant cell walls (Hotz & Gibson, 2007; Ribas‐Agustí et al., 2017). Polyphenols bioaccessibility depends on the matrix type and cooking method.…”
Section: External Factors Affecting the Nutraceutical Bioavailabilitymentioning
confidence: 99%
“…Pasta is a good source of carbohydrates and energy. One serving of 100 g of pasta (cooked, unenriched, without added salt) contains about 31 g of carbohydrates, 26.01 g starch, 1.8 g total dietary fibre, 5.8 g protein, and 0.93 g lipid (fat), and provides about 158 kcal [8]. When pasta is cooked al dente, it also has a low glycemic index, ranging around 32-40, depending on the pasta type [9].…”
Section: Introductionmentioning
confidence: 99%